POPULARIZATION OF WINTER SPORTS AS A FACTOR IN THE DEVELOPMENT OF SPORTS TOURISM (Physical Culture and Sport: Scientific Perspective, 2025)
The article examines the issue of popularization of winter sports as a factor in the development of sports tourism. The current state of winter sports and their impact on the tourism sector are analyzed. The key factors that determine the level of involvement of the population in winter sports, including economic accessibility, level of infrastructure and effectiveness of information support, are considered. The role of sports tourism in strengthening the economic potential of regions is outlined, in particular through the development of tourist complexes, increasing demand for services of the sports segment and attracting investment. The main methods of popularization of winter sports are identified, including the organization of mass sports events, creation of modern infrastructure and implementation of educational programs. Particular attention is paid to the environmental aspects of winter sports tourism development, including sustainable use of natural resources, introduction of environmental technologies in tourist areas and measures to minimize the negative impact on the environment. The positive impact of winter sports on the physical and psycho-emotional health of the population is noted. Active outdoor recreation helps to strengthen the cardiovascular system, improve endurance, coordination and reduce stress. The article emphasizes the need for an integrated approach to the popularization of winter sports to ensure the sustainable development of sports tourism. The prospects for further research in this area are considered separately, in particular, the possibility of using digital technologies to attract people to winter sports, as well as the adaptation of sports tourism to climate change. The author emphasizes the importance of an interdisciplinary approach and cooperation between sports organizations, travel companies and government agencies for the effective development of winter sports tourism.
Keywords: winter sports; sports tourism; popularization; tourism infrastructure; economic development; environmental sustainability; healthy lifestyle; digital technologies; climate change